Campania Preventability Assessment Committee (Italy): A Focus on the Preventability of Non-steroidal Anti-inflammatory Drugs' Adverse Drug Reactions - Sessa, Maurizio; Sportiello, Liberata; Mascolo, Annamaria; Scavone, Cristina; Gallipoli, Silvia; di Mauro, Gabriella; Cimmaruta, Daniela; Rafaniello, Concetta; Capuano, Annalisa (Frontiers in Pharmacology, 2017)
Purpose This study aims to investigate preventability criteria of adverse drug reactions (ADRs) involving non-steroidal anti-inflammatory drugs (NSAIDs) by analyzing individual case safety reports (ICSRs) sent through Campania region (Italy) spontaneous reporting system from July 2012 to October 2016. Methods For all the ICSRs that reported NSAIDs as suspected drug, a trained multidisciplinary team of Campania Pharmacovigilance Regional Centre composed of clinical pharmacologists and pharmacists with pluriannual experience in Pharmacovigilance assessed preventability by using the P-method. Results In all 19,039 ICSRs were sent to Campania Pharmacovigilance Regional Centre, of which 550 reported NSAIDs as suspected drug. In total, 94 cases (17.1%) out of 550 ICSRs were preventable. In the 94 preventable cases, 201 critical criteria were detected of which 182/201 (90.5%) related to healthcare professionals’ practices, 0/201 (0.0%) to drug quality, and 19/201 (9.5%) to patient behavior. The most detected critical criteria were the necessary medication not given (52/182; 28.6%), labelled drug–drug interaction (36/182; 19.7%), incorrect drug administration duration (31/182; 16.9%), wrong indication (26/182; 14.2%), therapeutic duplication (18/182; 10.0%), and documented hypersensitivity to administered drug or drug class (10/182; 5.6%). In seventeen (18.1%) preventable cases, there were 19 critical criteria involving non-compliance (15/19 critical criteria; 78.9%) and self-medication with the non-over-the-counter drugs (4/19 critical criteria; 21.1%). In all, 17 out 94 (18.1%) preventable cases involved over-the-counter drugs. Conclusion A call for action for Campania Pharmacovigilance Regional Centre is necessary in order to promote initiatives to increase the awareness of healthcare professionals and citizens on the risk associated with inappropriate use of NSAIDs.